KEMAMPUAN BERPIKIR TINGKAT TINGGI MAHASISWA CALON GURU DALAM MENGAJUKAN MASALAH MATEMATIKA SEKOLAH - Siti Nuriyatin; Soffil Widadah (Unisda Journal of Mathematics and Computer Science (UJMC), 2018)
A Teacher candidate requires competence in assessments of learning outcomes. A good assessment can measure the learning competencies that have been done. On the other hand, the school requires students have higher order thinking skills. Therefore, teachers must be able to perform learning that can increase higher order thinking skills students and their assessment. The purpose of this study was intended to investigate the ability of prospective mathematic teachers in problem posing. The levels of higher order thinking skills are analyze, evaluate, and create in Bloom’s Taxonomy. This research is a qualitative descriptive study. The research subject was Prospective Mathematic Teachers. Data collection technique is used through test and interview. The results of this study are as much as 5% of the research subjects were able at analyzes levels in problem posing. Most of them are on apply levels in problem posing. It can be conclude that most prospective mathematic teachers have no higher order thinking skills yet.